Alternative agriculture - National Research Council (U.S.). Committee on the Role of Alternative Farming Methods in Modern Production Agriculture (Washington, D.C. : National Academy Press, 1989)
Case studies of eleven farming operations across the United States test the economic impacts of alternative agricultural practices such as integrated pest management, crop rotation, manure management, low-density animal production systems, and crop diversification. Impact of U.S. federal regulations and policies on alternative farming is also considered.
Part 2. The case studies: Crop and livestock farming in Ohio: the Spray brothers -- A mixed crop and livestock farm in Southwest Iowa: the BreDahl Farm -- A diversified crop and livestock farm in Virginia: the Sabot Hill Farm -- A mixed crop and livestock farm in Pennsylvania: the Kutztown Farm -- Crop-livestock farming in Iowa: the Thompson Farm -- Tree fruits, walnuts, and vegetables in California: the Ferrari Farm -- Florida fresh-market vegetable production: integrated pest management -- Fresh grapes in California and Arizona: Stephen Pavich & Sons -- Integrated pest management in processing tomatoes in California: the Kitamura Farm -- Livestock farming in Colorado: Coleman Natural Beef -- Rice production in California: the Lundberg Family Farms. Glossary -- Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Alternative agriculture -- United States; Pests -- Integrated control -- United States -- Case studies; Agricultural systems -- United States -- Case studies; Systèmes agricoles -- États-Unis -- Cas, Études de; Agriculture -- Technologie appropriée -- États-Unis.; Animaux et plantes nuisibles -- Lutte intégrée contre -- États-Unis -- Études de cas; Systèmes agricoles -- États-Unis -- Études de cas; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; Agriculture; Ecologie; Agriculture biologique; Etats-Unis d'Amérique.; Agricultural systems; Alternative agriculture; Pests -- Integrated control; United States; Agrarpolitik; Agrarökologie; Biologische Landwirtschaft; Biologischer Landbau; Landwirtschaftlicher Betrieb; USA; Agricultural systems -- Case studies -- United States; Alternative agriculture -- United States; alternatieve landbouw; alternative farming; biologische landbouw; organic farming; vs; usa; gevalsanalyse; case studies; Alternative Farming; Organic Farming; Alternatieve Landbouw; Ecologische landbouw; Landbouwsystemen; Electronic books; Case studies